A CHEMICAL EQUILIBRIUM MODEL FOR METAL ADSORPTION ONTO BACTERIAL SURFACES - Fein J.B.; Daughney C.J.; Yee N.; Davis T.A. (My University, 1997)
This study quantifies metal adsorption onto cell wall surfaces of Bacillus subtilis by applying equilibrium thermodynamics to the specific chemical reactions that occur at the water-bacteria interface. We use acid/base titrations to determine deprotonation constants for the important surface functional groups, and we perform metal-bacteria adsorption experiments, using Cd, Cu, Pb, and Al, to yield site-specific stability constants for the important metal-bacteria surface complexes. The acid/base properties of the cell wall of B. subtilis can best be characterized by invoking three distinct types of surface organic acid functional groups, with pKa values of 4.82 +/- 0.14, 6.9 +/- 0.5, and 9.4 +/- 0.6. These functional groups likely correspond to carboxyl, phosphate, and hydroxyl sites, respectively, that are displayed on the cell wall surface. The results of the metal adsorption experiments indicate that both the carboxyl sites and the phosphate sites contribute to metal uptake. The values of the log stability constants for metal-carboxyl surface complexes range from 3.4 for Cd, 4.2 for Pb, 4.3 for Cu, to 5.0 for Al. These results suggest that the stabilities of the metal-surface complexes are high enough for metal-bacterial interactions to affect metal mobilities in many aqueous systems, and this approach enables quantitative assessment of the effects of bacteria on metal mobilities.